TRANSPLANTATION OF BONE MARROW CELLS AND UMBILICAL CORD BLOOD CELLS AS A WAY FOR CORRECTION OF AUTOIMMUNE MECHANISMS IN DEVELOPMENT OF DIABETES MELLITUS TYPE I - D. A. Velikiy; A. R. Zakirianov; O. M. Pozdnyakov; N. A. Onischenko (Вестник трансплантологии и искусственных органов)
In this review the modern conception of development of autoimmune diabetes mellitus was presented. Possibilities of immune disturbances correction and β-cells regeneration at transplantation of bone marrow and umbilical cord blood cells were considered.